Relation of NT-probnp levels and cardiovascular disease risk factors in lean women with polycystic ovary syndrome - YOLDEMİR, AHMET TEVFİK (TAYLOR & FRANCIS INC, 2019)
Women with polycystic ovary syndrome (PCOS) often have cardiovascular disease (CVD) risk factors. N-terminal fragment of brain natriuretic peptide (Nt-probnp) is used as a diagnostic and prognostic marker for CVD. The aim of this study was to evaluate whether Nt-probnp is increased in lean PCOS patients. A total of 110 lean (BMI < 25 kg/m(2)) PCOS patients and 80 age and BMI matched healthy lean controls were included in this study. Serum Homeostatic Model Assessment-Insulin Resistance (HOMA-IR), Matsuda insulin sensitivity index (ISI), Nt-probnp, C-reactive protein (CRP), androgen and lipid levels were measured. Serum Nt-probnp levels were significantly higher in the PCOS group. Hyperandrogenic PCOS patients had higher Nt-probnp levels. There were significant correlations between serum Nt-probnp and total testosterone, total cholesterol, HOMA and Matsuda levels. Linear regression analysis showed that Matsuda ISI and fasting insulin levels significantly affected the Nt-probnp levels (R-2 of the model = 0.763; p<.0001).IMPACT STATEMENT What is already known on this subject? Many risk factors for cardiovascular disease (CVD) including insulin resistance, dyslipidaemia, hypertension and hyperandrogenism may be found in young women with polycystic ovary syndrome (PCOS), although evidence for CVD in lean women with PCOS is limited. N-terminal fragment of brain natriuretic peptide (NT-probnp) is a high predictive marker regarding of CVD, especially in patients without overt CVD. There have been contradictory results regarding Nt-probnp levels in PCOS patients and there have not been any effective studies regarding the relation between CVD risk factors and Nt-probnp levels for lean PCOS patients. What the results of this study add? This study found increased Nt-probnp levels in lean PCOS patients, which may indicate a positive correlation with risk for CVD. Strong relations were also found between Nt-probnp levels and increased insulin resistance, dyslipidaemia, decreased insulin sensitivity and hyperandrogenism. Lean PCOS patients have increased risk factors for CVD, and these risk factors are correlated with Nt-probnp levels. Nt-probnp is more affected by increased fasting insulin and decreased insulin sensitivity. What are of these findings for clinical practice and/or further research? Lean PCOS patients should be evaluated for CVD. Further prospective controlled studies are needed in order to predict the long-term risk of developing CVD in lean PCOS patients.
Keywords: N-terminal fragment of brain natriuretic peptide; cardiovascular disease; polycystic ovary syndrome; dyslipidaemia; Matsuda insulin sensitivity index; BRAIN NATRIURETIC PEPTIDE; INSULIN-RESISTANCE; GLUCOSE-TOLERANCE; OBESE WOMEN; DYSLIPIDEMIA; PREVALENCE; ADOLESCENT; EVENTS; HEALTH; COMMON